2014
DOI: 10.1017/s0033291714001640
|View full text |Cite
|
Sign up to set email alerts
|

Age of onset and course of major depressive disorder: associations with psychosocial functioning outcomes in adulthood

Abstract: Background Major depressive disorder (MDD) that onsets by adolescence is associated with various deficits in psychosocial functioning. However, adolescent-onset MDD often follows a recurrent course, which may drive its associated impairment. Methods To tease apart these two clinical features, we examined the relative associations of age of onset (adolescent versus adult) and course (recurrent versus single episodes) of MDD with a broad range of psychosocial functioning outcomes assessed in early adulthood. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
69
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 34 publications
(66 reference statements)
1
69
1
Order By: Relevance
“…We are aware of only two studies, from our own group, that explicitly compared personality traits for early-onset and later-onset MDD. Although we found higher negative emotionality for both early- and later-onset MDD relative to no MDD (Wilson et al, 2014; Wilson et al, in press), and we also found that negative emotionality in adolescence prospectively predicted the onset of MDD in adulthood (Wilson et al, 2014), we found little evidence of differences in negative emotionality or positive emotionality in adulthood as a function of age of onset once course was accounted for (Wilson et al, in press). A handful of studies have considered effects of personality traits for the course of depressive disorders.…”
Section: Risk Factors For Mddcontrasting
confidence: 71%
See 3 more Smart Citations
“…We are aware of only two studies, from our own group, that explicitly compared personality traits for early-onset and later-onset MDD. Although we found higher negative emotionality for both early- and later-onset MDD relative to no MDD (Wilson et al, 2014; Wilson et al, in press), and we also found that negative emotionality in adolescence prospectively predicted the onset of MDD in adulthood (Wilson et al, 2014), we found little evidence of differences in negative emotionality or positive emotionality in adulthood as a function of age of onset once course was accounted for (Wilson et al, in press). A handful of studies have considered effects of personality traits for the course of depressive disorders.…”
Section: Risk Factors For Mddcontrasting
confidence: 71%
“…Wilson et al (2014) found that negative emotionality was concurrently and prospectively associated with both recurrent/chronic MDD and nonrecurrent/nonchronic MDD, relative to no MDD, but positive emotionality was concurrently and prospectively associated only with recurrent/chronic MDD (regardless of whether it onset early or later). Wilson et al (in press) explicitly compared personality traits for recurrent and single-episode MDD, and found that recurrent MDD predicted lower positive emotionality and higher negative emotionality. Notably, Wilson et al (in press) found the lowest positive emotionality and highest negative emotionality for individuals with early-onset, recurrent MDD.…”
Section: Risk Factors For Mddmentioning
confidence: 99%
See 2 more Smart Citations
“…The significant increase in adolescence of mood disorders, particularly depression, as well as suicidal [5] and other self-harm behaviors [6], and the impact on all areas of adolescent functioning underscore the public health risk of this age group. The association of recurrent adolescent depression with adult depression and dysfunction [7], as well as with selfharm behaviors [8], emphasizes the importance of early identification and treatment of youth at risk for depression.…”
mentioning
confidence: 99%